Cyclic fatigue, torsional failure, and flexural resistance of rotary and reciprocating instruments - Ribeiro Camargo, Carlos; Bittencourt, Tatiane [UNESP]; Hasna, Amjad [UNESP]; Palo, Renato [UNESP]; Talge Carvalho, Claudio [UNESP]; Valera, Marcia [UNESP] (Wolters Kluwer, 2020)
Aim: The aim was to compare cyclic fatigue, torsional failure, and flexural resistance of NiTi endodontic files: Hyflex CM (HYF), Genius files (GEN), WaveOne Gold (WOG), and ProTaper Universal (PTU). Materials and Methods: Fifteen files of each brand were used in cyclic fatigue test and other fifteen files for flexural test and torsional failure test. To the cyclic fatigue test, used torque limit and revolutions per minute were set according to the respective manufacturer guidelines. The test was performed under deionized water at 36°C, and all files were tested in a 3 mm radius of curvature with an angle of curvature of 60°, time of the fracture was recorded. Torsional fatigue test was performed in the torsional machine (Instron MT, USA), recording the fractured time and torque data by the machine software. Flexural fatigue test was performed in 60° of curvature. All data were statistically analyzed by one-way analysis of variance, and Tukey test for multiple comparisons. Results: Cyclic fatigue (seconds)= HYF: 744.1 ± 231.9/GEN: 477.3 ± 220.5/WO: 278.4 ± 57.0/PTU: 152.4 ± 65.2; torsional failure (N × cm)= HYF: 6.85 ± 1.484/GEN: 6.55 ± 0.828/WOG: 5.73 ± 0.360/PTU: 4.43 ± 0.900; flexural resistance (N × mm)= HYF: 0.33 ± 0.294/GEN: 0.19 ± 0.136/WOG: 0.98 ± 0.216/PTU: 1.85 ± 0.276. Conclusion: HYF and GEN showed the best results for cyclic fatigue, torsional failure, and flexural resistance, followed by WOG and PTU.